Neutrophil to Lymphocyte Ratio and Platelet to Lymphocyte Ratio as Markers of Disease Activity in Rheumatoid Arthritis - Hazrat Hussain; Muhammad Asghar; . Naila; . Musa; . Zeeshan; Alam Zeb (Pakistan Journal of Health Sciences, 2026)
Rheumatoid arthritis (RA) is an inflammatory disease that adversely affects quality of life by impairing joint function. Objectives: To examine the use of NLR and PLR as activity indicators in RA. To ascertain their independent prediction by examining the relationships between these DAS28-ESR fractions of disease activity and other conventional inflammatory indicators like ESR and CRP. Methods: This study involved 230 rheumatoid arthritis patients assessed in the Department of Rheumatology, Khyber Teaching Hospital, Peshawar. Disease Activity Score 28 (DAS28) was used to assess disease activity together with clinical parameters, erythrocyte sedimentation rate, C-reactive protein, neutrophil-to-lymphocyte ratio, platelet-to-lymphocyte ratio, and others. Multivariate regression and rank correlation (Spearman) were done to determine the relationship between these biomarkers and DAS28. Results: Significant positive correlations were identified between inflammatory markers and activity of the disease (DAS28), with NLR (ρ = 0.772, p